PENGARUH PENDEKATAN BERMAIN TERHADAP HASIL PEMBELAJARAN BERMAIN SEPAKBOLA - Septiana, Keny (2017)
Tujuan penelitian ini untuk mengetahui pengaruh pendekatan bermain terhadap hasil pembelajaran bermain sepakbola. Metode penelitian yang adalah metode eksperimen. Teknik pengambilan sampel dalam penelitian ini adalah Random Sampling. Instrument yang digunakan adalah Instrumen yang digunakan dalam penelitian ini yaitu tes penampilan bermain sepakbola menggunakan GPAI (Game Performance Assesment Instrument). Berdasarkan uji normalitas diperoleh hasil dalam pre-test pendekatan bermain Lhitung 0,188 dan pembelajaran kovensional Lhitung 0,189, kemudian saat post-test pendekatan bermain Lhitung 0,188 dan pembelajaran konvensional Lhitung 0,182. Jadi data yang diperoleh berdistribusi normal karena tidak lebih dari Ltabel 0,190. Hasil uji homogenitas diperoleh hasil dari pre-test sebesar 1,039 dan post-test sebesar 1,483. Jadi data yang diperoleh dari hasil pre-test dan post-test adalah homogen karena karena lebih kecil dari Ftabel sebesar 2,15. Uji hipotesis diperoleh hasil hipotesis bahwa nilai thitung (6,116) ≥ ttabel (1,725) maka H0 ditolak. Dengan demikian Terdapat pengaruh yang signifikan pendekatan bermain terhadap hasil pembelajaran bermain sepakbola (Siswa kelas X SMAN 23 Bandung).;--- The purpose of this research to know the influence of approach play to the results of learning played football. The research method is experimental method. The technique collecting of samples in the research is Random Sampling. The instrument used in this research is test appearance play football use GPAI (Game Performance Assessment Instrument). Based on the normality obtained by the results in pre-test approach play Lcalculate 0,188 and conventional learning Lcalculate 0,189 and then when post-test approach play Lcalculate 0,188 and conventional learning Lcalculate 0,182. So the data obtainable distributed normal because no more than Llist 0,190. Test result of homogeneity obtained from the pre-test as big as 1,039 and post-test as big as 1,483. So the data from the results pre-test and pot-test is homogeneous because smaller than Flist as big as 2,15. Hypothesis test result was obtained on the hypothesis that the total value of tcalculate (6,116) ≥ tlist (1,725) then H0 rejected. Thus there a significant approaches playing the results of learning to play football. (Student in class X SMAN 23 Bandung).The purpose of this research to know the influence of approach play to the results of learning played football. The research method is experimental method. The technique collecting of samples in the research is Random Sampling. The instrument used in this research is test appearance play football use GPAI (Game Performance Assessment Instrument). Based on the normality obtained by the results in pre-test approach play Lcalculate 0,188 and conventional learning Lcalculate 0,189 and then when post-test approach play Lcalculate 0,188 and conventional learning Lcalculate 0,182. So the data obtainable distributed normal because no more than Llist 0,190. Test result of homogeneity obtained from the pre-test as big as 1,039 and post-test as big as 1,483. So the data from the results pre-test and pot-test is homogeneous because smaller than Flist as big as 2,15. Hypothesis test result was obtained on the hypothesis that the total value of tcalculate (6,116) ≥ tlist (1,725) then H0 rejected. Thus there a significant approaches playing the results of learning to play football. (Student in class X SMAN 23 Bandung).